Tailoring of Cityscape for the Elderly - Mahdi Zandieh (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: Cities have experienced a boost in their population over last decades however, they have not developed along with such fundamental changes. Due to neglecting population alteration and ignoring vulnerable groups of citizens, urban development has been resulted in social exclusion. Methods & materials: In this regard, elderly is one of the mentioned groups who incur multitude of difficulties in city. Notwithstanding their willingness for participating in social interactions and using urban spaces, they are divested of favorable urban spaces providing them the possibility of independent life. In other words, elderly would like to demonstrate their abilities through accomplishing their responsibilities and communicating with their neighbors, as their springtime. Results: However, do our cities enjoy spaces meeting elderly needs and do they provide appropriate facilities for them? There is no doubt that there are many factors contributing in shaping a city, like urban land use, physical context, access and cityscape. This article investigates the last factor in urban design affecting elderly social interactions. It is evident that this is a crucial factor which plays an important role in routing and it is inextricably linked to elderly needs and their visual and mental impairments. Conclusion: The article is looking for solutions through exploring the matter in Qeytarieh District of Tehran, as a case study. At the end related guidelines will represent.